2018
DOI: 10.1093/annonc/mdy106
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab may improve quality of life, but not overall survival in glioblastoma: an epidemiological study

Abstract: This epidemiological study of a small, but clinically well-annotated patient cohort fails to support the assumption that the strong increase of bevacizumab use since 2010 improved survival in glioblastoma although clinical benefit associated with decreased steroid use may have been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 13 publications
0
68
1
1
Order By: Relevance
“…A combination of bevacizumab and lomustine is considered for treatment of recurrent GBM patients with rapidly progressing disease [ 55 ]. However, in most cases, these chemotherapies either in combination or alone have failed to show prolongation of overall survival in recurrent GBM patients [ 56 , 57 ]. Therefore, irrespective of the treatment method, most patients diagnosed with primary GBM die within two years.…”
Section: Treatment Options For Gbm/history Of Gbm Treatmentmentioning
confidence: 99%
“…A combination of bevacizumab and lomustine is considered for treatment of recurrent GBM patients with rapidly progressing disease [ 55 ]. However, in most cases, these chemotherapies either in combination or alone have failed to show prolongation of overall survival in recurrent GBM patients [ 56 , 57 ]. Therefore, irrespective of the treatment method, most patients diagnosed with primary GBM die within two years.…”
Section: Treatment Options For Gbm/history Of Gbm Treatmentmentioning
confidence: 99%
“…Bevacizumab (Avastin), an anti-VEGF antibody, has been shown to be effective in the treatment of a number of solid cancers, including metastatic colorectal cancer, renal cell cancer and non-small cell lung cancer [37][38][39][40]. Bevacizumab has been approved for use in the treatment of GBM, despite reports of limited improvement in overall survival [41][42][43]. A Phase III study has reported an increase in progression-free survival and improved quality of life, however, an increase in adverse events in patients receiving bevacizumab compared to a placebo was also observed [41,42].…”
Section: Advances In Treatments For Gbmmentioning
confidence: 99%
“…Bevacizumab has been approved for use in the treatment of GBM, despite reports of limited improvement in overall survival [41][42][43]. A Phase III study has reported an increase in progression-free survival and improved quality of life, however, an increase in adverse events in patients receiving bevacizumab compared to a placebo was also observed [41,42].…”
Section: Advances In Treatments For Gbmmentioning
confidence: 99%
“…Initial clinical studies of glioblastoma showed that bevacizumab delayed progression from ~7 to ~10 months, but did not impact overall survival (~16 months) [1]. Others found similar results [2]. Newer bevacizumab regimens with 100 mg/m 2 /day cycles of temozolomide and newer studies of lower bevacizumab doses have indicated some survival benefits [3].…”
Section: Introductionmentioning
confidence: 99%